Mitske podobe o "Življenju na mreži" - Oblak, Tanja (Teorija in praksa, 2000)
The article offers a precise and at the same time an extensive insight into the problem field, exposed by the modern scientific discourse on communication technologies. These questions deal with the changing relations between various understandings of virtual reality, cyber space and computer mediated communication. These increasingly involve numerous viewpoints on social phenomena, such as virtual community and virtual identity. The authoress attempts to explain the mentioned relations as a reflection of the arising communication practices supported by computer technologies. She is interested in the relations between space and communication, body and identity, individual's action and community. From the critical position on exaggerated optimistic ideas about the influence of computer technologies on our everyday life, she attempts to verify some, for more then decade present, mythic images and at the same time call attention to the real social relations which play an important role in this context.
Keywords: Mitologija; Mythology; Internet; Everyday life; Vsakdanje življenje; navidezna resničnost; informacijska tehnologija; information technology; množične komunikacije; kibernetika; družbeni vidik; identiteta